Peran pt bidang kejuruan dalam menyiapkan guru profesional - Luckie Sojow (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2011)
THE ROLE OF THE VOCATIONAL INDUSTRY IN PREPARING PROFESSIONAL TEACHERSSchool of Engineering in the Higher Educational Institutions produce professional teachers for vocational schools and training institutions who are able to meet the need of community. The curriculum should always keep up date with the needs of market. There two approaches in developing professional teacher: individual and team. Individual approach is developed by the individual self, and input might come from upper authorities, experts, and peer which is grouped by subject matter. On the other hand team approach, the system puts trust more on group of individuals that have shared goals to achieved rather than on individual. Management at study program level, as a primary practical community, can be managed holistically and in integrative ways.